Assessing the energy expenditure of elite female soccer players: A preliminary study - Mara, J. K.; Thompson, K. G.; Pumpa, K. L. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to assess the total and exercise energy expenditure of elite female soccer players during a training week. Eight elite female soccer players wore SenseWear Mini Armbands (SWAs) for 7 consecutive days during the preseason phase of a national league competition. In addition, players wore 15-Hz GPSports tracking devices during 4 training sessions and a friendly game. Total energy expenditure, exercise energy expenditure, and training and game demands were collected from the SWA and GPSports devices. Mean daily energy expenditure for the game day, training days, and rest days were 12,242 kJ (SD = 603 kJ), 11,692 (SD = 274 kJ), and 9,516 (SD = 369 kJ), respectively, with significant differences shown between activities (p < 0.001, partial n^2 = 0.357), as well as between individual days (p < 0.001, partial n^2 = 0.517). Mean values for energy expenditure during the friendly game (mean = 2,695 kJ, SD = 301 kJ) and training sessions (mean = 2,538 kJ, SD = 316 kJ) were similar (p = 0.278, Cohen's d = 0.5). However, there were significant differences found between individual training sessions (p = 0.001-0.035). Total and exercise energy expenditure differs throughout the week in female soccer players. Nutritional intake should be adjusted accordingly to avoid energy imbalances for optimal performance and recovery.